Pengaruh Penggunaan Lahan terhadap Kualitas Air Permukaan di Sungai Kampar - Indriyani; Hani Burhanuddin (Bandung Conference Series: Urban & Regional Planning, 2021)
Abstract. The occurrence of population growth and human activities are factors that affect economic growth. Population growth which is an influence in economic growth also has an effect on increasing the need for land to support human activities. The increasing need for land to meet economic needs and the availability of land will continue to have an impact on land conversion activities. Economic activities and land use of Pelalawan Regency in the last 10 years show some unsustainable land management. From the activities carried out by the people of Pelalawan Regency, especially on the banks of the Kampar River resulting in polluted river water, these activities affect the content of soluble minerals that change the quality of the river water, these activities affect the content of soluble minerals, thus changing the quality of the river water. . Based on the Qur'an Surah Al-Baqarah verse 11 which is used as the spiritual foundation of this research, it is necessary to make improvements to the environmental damage that has occurred. According to Government Regulation No. 82 of 2001 which regulates Water Quality Management and Water Pollution Control, water pollution control is a step in efforts to prevent and control water pollution and restore water quality. This research was conducted in Pelalawan Regency, Riau Province. This study aims to determine the effect of land use on the quality of water sources used by the community in Pelalawan Regency. The analysis used in this research is Land Use Analysis, Water Quality Analysis and Correlation Analysis. The results of this analysis indicate that land uses that have the potential to affect water quality are plantations, settlements, swamps and rice fields based on the weighted results. For the water quality contained in Sample 1 of Kuala Terusan Village, Sample 2 of Pangkalan Kerinci Village, and Sample of 3 Villages Often included in the category of heavily polluted with an average value of > 10 , the land that dominates in these 3 samples is plantation land, settlements, forests and swamp. Based on the results of correlation analysis using the Pearson correlation method, land use that has a very strong correlation that has an influence on water quality is the use of plantation land and forest land. The final results of the analysis will be used as consideration in the management and control of land around the Kampar River area. Abstrak. Terjadinya pertumbuhan penduduk dan aktivitas manusia menjadi faktor yang mempengaruhi pertumbuhan ekonomi. Pertumbuhan penduduk yang menjadi pengaruh dalam pertumbuhan ekonomi ini juga memberikan pengaruh terhadap peningkatan kebutuhan lahan guna mendukung aktivitas manusia. Kebutuhan lahan yang meningkat untuk memenuhi kebutuhan ekonomi dan ketersediaan lahan yang tetap berdampak pada kagiatan alih fungsi lahan. Dari kegiatan yang dilakukan masyarakat Kabupaten Pelalawan khususnya di tepi Sungai Kampar mengakibatkan air sungai tercemar, kegiatan tersebut mempengaruhi kandungan mineral-mineral yang dapat larut sehingga mengubah kualitas air sungai tersebut, kegiatan tersebut mempengaruhi kandungan mineral-mineral yang dapat larut sehingga mengubah kualitas air sungai tersebut. Diperlukannya melakukan perbaikan terhadap kerusakan lingkungan yang telah terjadi di dalam Peraturan Pemerintah No. 82 Tahun 2001 yang mengatur tentang Pengelolaan Kualitas Air dan Pengendalian Pencemaran Air, pengendalian pencemaran air merupakan suatu langkah dalam upaya pencegahan dan penanggulangan pencemaran air serta pemulihan terhadap kualitas air. Penelitian ini dilakukan di Kabupaten Pelalawan, Provinsi Riau. Penelitian ini bertujuan untuk mengetahui pengaruh penggunan lahan terhadap kualitas sumber air yang digunakan oleh masyarakat di Kabupaten Pelalawan . Analisis yang digunakan dalam penelitian ini yaitu Analisis Penggunaan Lahan, Analisis Kualitas Air dan Analisis Korelasi. Hasil Analisis ini menunjukan bahwa penggunaan lahan yang dominan berpotensi memberikan pengaruh terhadap kualitas air adalah perkebunan . Untuk kualitas air berdasarkan status mutu air termasuk pada kelas buruk dengan skor -44, dan menurut indeks pencemaran air pada Sample 1 Desa Kuala Terusan, Sample 2 Desa Pangkalan Kerinci, dan Sample 3 Desa Sering termasuk kedalam kategori cemar berat dengan nilai rata – rata >10 , lahan yang mendominasi di 3 sample ini adalah lahan perkebunan, permukiman, hutan dan rawa. Berdasarkan hasil analisis korelasi menggunakan metode korelasi Pearson penggunaan lahan yang memiliki korelasi sangat kuat yang memberikan pengaruh terhadap kualitas air adalah penggunaan lahan perkebunan dan lahan hutan. Hasil akhir analisis akan dijadikan sebagai bahan pertimbangan dalam pengelolaan dan pengendalian lahan di sekitar kawasan Sungai Kampar.